Geometrically Complex, Relatively Weak, and Subcritically Stressed Lembang Fault May Lead to a Magnitude 7.0 Earthquake - Palgunadi, Kadek Hendrawan; Simanjuntak, Andrean Vesalius Hasiholan; Ry, Rexha Verdhora; Daryono, Mudrik Rahmawan; Widiyantoro, Sri; Warnana, Dwa Desa; Triahandini, Agnis; Syaifuddin, Firman; Ahmadiyah, Adhatus Solichah; Sirait, Anne Meylani Magdalena; Suryanto, Wiwit (Directorate for Research and Community Services, Institut Teknologi Bandung, 2025)
The Lembang Fault is one of the major faults in the province of West Java, approximately 10 km north of its capital, Bandung, a city inhabited by more than 2 million people. The fault exhibits distinct geometrical characteristics in its 29 km length, transitioning from normal, strike-slip, to vertical faulting mechanisms. Two studies have evidence of a normal fault with a dip direction to the north and a thrust fault with a dip direction to the south. Despite the lack of significant recorded earthquakes, the Lembang Fault is active and poses a high seismic hazard to the surrounding region. Previous deformation studies estimate that the fault could produce earthquakes of magnitude 6.7 to 7.0, though these estimates do not account for the fault's unique geometry, which includes bends at both its eastern and western ends. This geometrical complexity can significantly affect slip distribution, potentially leading to over- or underestimating earthquake magnitude. In this study, we assess the earthquake potential of the Lembang Fault using 3D dynamic rupture simulations that incorporate the fault's geometrical complexity, 3D velocity structure, and plastic deformation. Our simulations indicate that the fault's complex geometry enhances rupture slip to the east while halting it to the west, resulting in rupture along 80% of the fault's total length. However, according to our model, a self-sustained runaway rupture scenario occurs only if the fault is characterized by relatively weak apparent strength, subcritical stress, and overpressurization. This worst-case scenario could result in a magnitude 7.0 earthquake, posing a significant threat to the densely populated nearby city. Therefore, our findings have crucial implications for seismic hazard assessment around the Lembang Fault.